Is the Expression of Love Feminized? A Test and Extension of Cancian`s Hypothesis - Huić, Aleksandra (Array, 2011)
Cancian (1986) argued that men and women have been socialized to show love in different ways, with women showing love by expresing positive emotions directly and men by doing activities together, helping out with domestic chores, and showing sexual interest. Furthermore, she argued that integrating both feminine expressivity and masculine instrumentality is what makes a relationship more loving for both men and women. Our aim was to test her ideas by directly asking husbands and wives how they show love. We tested 302 Croatian married couples of different ages (20-82 years) and various urban/rural backgrounds. Length of marriage varied between one month and 57 years. We administered the Love Scale (Braiker and Kelly, 1979) and The Ways of Showing Love Scale (constructed for this study) which measures 3 expressive and 3 instrumental factors. Results suggest that specific types of expressive and instrumental ways of showing love need to be considered. Expectedly , it is more characteristic for women than for men to show love by doing housework and being supportive. Showing love with sex and runing errands is more characteristic for men. Contrary to Cancian, there are no gender differences when it comes to directly showing affection or putting one's needs before partner's. A significant main effect of love seems to confirm Cancian's androgynous perspective of love - both men and women who love more use more of both expressive and instrumental ways of showing love than do men and women who love less.